2018
DOI: 10.1096/fj.201700300r
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxic very‐long‐chain ceramides cause mitochondrial dysfunction, oxidative stress, and cell death in cardiomyocytes

Abstract: Accumulating data support a role for bioactive lipids as mediators of lipotixicity in cardiomyocytes. One class of these, the ceramides, constitutes a family of molecules that differ in structure and are synthesized by distinct enzymes, ceramide synthase (CerS)1-CerS6. Data support that specific ceramides and the enzymes that catalyze their formation play distinct roles in cell function. In a mouse model of diabetic cardiomyopathy, sphingolipid profiling revealed increases in not only the CerS5-derived ceramid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
133
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 73 publications
2
133
0
2
Order By: Relevance
“…It should be by guest, on May 11, 2018 www.jlr.org There is some discrepancy in which VDAC isoform is more critical for regulation of intracellular ATP, which is likely to be cell-type specific (51,52). Most recently, excess elevation of ceramide has been shown to induce mitophagy, suggesting that the physiological function of ceramide as discussed in our study requires limitation of its concentration at mitochondria (88,89). While ATP levels observed in our study are consistent with CATregulated ATP release under normal physiological conditions, several studies have shown that under pathophysiological conditions, reduction of ATP levels are concurrent with decreased mitochondrial motility and increased fragmentation (44,(90)(91)(92).…”
Section: Discussionsupporting
confidence: 75%
“…It should be by guest, on May 11, 2018 www.jlr.org There is some discrepancy in which VDAC isoform is more critical for regulation of intracellular ATP, which is likely to be cell-type specific (51,52). Most recently, excess elevation of ceramide has been shown to induce mitophagy, suggesting that the physiological function of ceramide as discussed in our study requires limitation of its concentration at mitochondria (88,89). While ATP levels observed in our study are consistent with CATregulated ATP release under normal physiological conditions, several studies have shown that under pathophysiological conditions, reduction of ATP levels are concurrent with decreased mitochondrial motility and increased fragmentation (44,(90)(91)(92).…”
Section: Discussionsupporting
confidence: 75%
“…2007; Law et al . 2018), induce Ca 2+ dysregulation (Egnatchik et al . 2014; Arruda & Hotamisligil, 2015), alter mitochondrial function (Hsu et al .…”
Section: Discussionmentioning
confidence: 99%
“…They may also reflect changes in the composition and function of cellular membranes within tissues, because in addition to the generation of plasma ceramides by secreted sphingomyelinases, ceramides are also secreted by parenchymal tissues 21, 22. Given observations that ceramides accumulate in the myocardium in the setting of metabolic cardiomyopathy and HF, and given that accumulation of ceramides promotes cardiomyocyte oxidative stress and mitophagy, it is possible that enhanced ability to export very–long‐chain ceramides from tissues underlies the inverse relationships between plasma ratios of C24:0/C16:0 and CHD and mortality 23, 24. Future studies will be required to elucidate the relation of plasma ratios to ceramide content in specific tissues and how this affects the pathogenesis of vascular disease and related outcomes.…”
Section: Discussionmentioning
confidence: 99%